Transferable and Flexible Artificial Memristive Synapse Based on WOx Schottky Junction on Arbitrary Substrates. (4th November 2018) - Lin, Ya; Zeng, Tao; Xu, Haiyang; Wang, Zhongqiang; Zhao, Xiaoning; Liu, Weizhen; Ma, Jiangang; Liu, Yichun
Abstract: The absence of an effective approach to achieve free‐standing inorganic memristors seriously hinders the development of transferable artificial synapses. Here, a transferable WO x ‐based memristive synapse is demonstrated using a nondestructive water‐dissolution method in which the NaCl substrate is selected as the sacrificial layer due to its thermotolerance and water‐solubility. The essential synaptic learning functions are achieved to comprehensively mimic the biological synapse, such as short‐term/long‐term plasticity, paired‐pulse facilitation, and spike‐timing‐dependent plasticity. This artificial synapse can be transferred and conformed onto various unconventional substrates to manifest the flexibility, 3D conformality, and biocompatibility. There is no mechanical damage during the transfer process, and all these transferred devices present excellent synaptic emulations. The memristive behavior shows no degeneration after large‐angle bending or 100 times bending tests. This result may pave a feasible way for the realization of wearable neuromorphic computing systems in the future. Abstract : Using a nondestructive water‐dissolution method, a transferable WO X memristor is demonstrated when selecting NaCl substrate as the sacrificial layer. The synaptic devices are transferred onto diverse substrates, presenting excellent flexibility and high mechanical endurance. The essential functions of synaptic plasticity are obtained in the device on the bent state. The work offers a feasible method to enable inorganic memristors for transferable applications.